"I am not just a place for implementation. I should be a partner": a qualitative study of patient-centered care from the perspective of diabetic patients in Saudi Arabia - Reeham Ahmed Alkhaibari; Jennifer Smith-Merry; Rowena Forsyth (BMC, 2023)
Abstract Introduction Patient involvement in care is a major component of high quality of care and is becoming recognized worldwide with many beneficial for improving patient outcomes. However, a little is known about patient involvement in the Middle East region and Saudi Arabia in particular. Objectives To evaluate patients' perceptions of their involvement during their interactions with healthcare providers in Saudi Arabia. Methods A qualitative exploratory study using semi structured interview was conducted from February 2022 to March 2022. Responses were transcribed and analyzed using a thematic analysis approach. Results We conducted seven interviews with patients with diabetes ranging in age from 19 to 69 years old. We identified the following themes:1) patients' perceptions of their involvement in care, 2) barriers to patient involvement, 3) effective communication, 4) empathy, and 5) culture. We found that patients had minimal knowledge of patient involvement in care. Conclusion There is a clear need to improve education and awareness of patient involvement in Saudi Arabia. By educating patients about the possibilities of patient involvement and explaining their role it will make it easier for patients to understand appropriate levels of involvement. In addition, there is a need to understand the patient-centred care culture in Saudi Arabia through establishing frameworks with the focus on culture and patient-centred healthcare delivery.